Exploring Relationship Marketing Tactics & Customer Loyalty: Issues in the Malaysian Mobile Telecommunication Sector - Lennora Putit; Mohamad Fariz Abdullah (Journal of International Business, Economics and Entrepreneurship)
Most of today’s business firms are facing numerous challenges in sustaining customer loyalty due to a ferocious competitive environment. This study explores issues on relationship marketing and customer loyalty within the mobile telecommunications sector. In-depth interviews with targeted respondents were conducted to understand their initial perceptions on relationship marketing tactics issues and its influence on customer loyalty. Specifically, the study aims to acquire deeper insights into the motivational drives behind customer loyalty amongst different classes of mobile phone users. Qualitative data were collected using a digital voice tape-recorder, while the transcribing and coding processes were carried out using qualitative software called ATLAS.TI version 7.0. Based on thematic analyses, the findings have identified several themes such as trust, branding, alternative attractiveness, emotions, service quality, price perception, switching barriers, and commitment. Further results revealed suggestions on how to strengthen customer loyalty behaviour in the mobile telecommunications market.